Enabling miniaturised personalised diagnostics: from lab-on-a-chip to lab-in-a-drop. Issue 19 (29th August 2017) - Koo, Kevin M.; Wee, Eugene J. H.; Wang, Yuling; Trau, Matt
Abstract : "Lab-in-a-drop": a miniaturised fabrication-free diagnostics platform by which traditional bioassays are downsized into a droplet and programmed for convenient detection. Abstract : The concept of personalised diagnostics is to direct accurate clinical decisions based on an individual's unique disease molecular profile. Lab-on-a-chip (LOC) systems are prime personalised diagnostics examples which seek to perform an entire sample-to-outcome detection of disease nucleic acid (NA) biomarkers on a single miniaturised platform with minimal user handling. Despite the great potential of LOC devices in providing rapid, portable, and inexpensive personalised diagnosis at the point-of-care (POC), the translation of this technology into widespread use has still been hampered by the need for sophisticated and complex engineering. As an alternative miniaturised diagnostics platform free of precision fabrication, there have been recent developments towards a solution-based lab-in-a-drop (LID) system by which an entire laboratory-based diagnostics workflow could be downscaled and integrated within a singular fluid droplet for POC detection of NA biomarkers. In contrast to existing excellent reviews on miniaturised LOC fabrication and individual steps of NA biomarker sensing, we herein focus on miniaturised solution-based NA biosensing strategies suited for integrated LID personalised diagnostics development. In this review, we first evaluate the three fundamental bioassay steps for miniaturised NA biomarker detection: crude sample preparation, isothermal target amplification, and detection readout of amplicons. Then, we provide insights into research advancements towards a functional LID system which integrates all three of the above-mentioned fundamental steps. Finally, we discuss perspectives and future directions of LID diagnostic platforms in personalised medicine applications.